Evaluation of an ultrafiltration membrane for the removal of fish viruses and bacteria in aquaculture water - Mota, Vasco C.; Brenne, Hanne; Kojen, Morten; Marhaug, Kine Rivers; Jakobsen, Margit Ertresvåg (Frontiers in Marine Science, 2022)
Ultrafiltration (UF) membranes are used to successfully remove waterborne virus and bacteria from wastewater and drinking water. However, UF membrane application in aquaculture water treatment is limited. In this study we evaluate the performance of a capillary polyethersulfone UF membrane to remove two benchmark waterborne fish pathogens: i) the infectious pancreatic necrosis virus - IPNV, which is an unenveloped icosahedral virus, and ii) the bacterium Aeromonas salmonicida, which is a Gram-negative, facultative anaerobic bacilli. Moreover, the UF membrane bench-scale unit was tested at two temperatures according to salmonid aquaculture: low (4 - 7℃) and high (16 - 19℃). Sterilised natural seawater was spiked with laboratory cultured pathogens, the water was filtrated, and the membrane permeate collected. Both pathogen solution and permeate were evaluated using a cell culture method to estimate the colony-forming units (CFU/ml) for bacteria presence, a median tissue culture infectious dose (TCID50/ml) assay for virus presence, and real-time quantitative polymerase chain reaction (RT-qPCR) for both bacteria and virus presence. The membrane permeate was negative for both virus and bacteria for all analysis and for both low and high temperatures. The results from this bench-scale study are encouraging for the application of UF membrane technology in aquaculture water treatment to prevent virus and bacteria outbreaks. Further studies should validate this UF membrane technology results in commercial aquaculture conditions.